Metodologi Pemecahan Masalah Analisis dan Evaluasi Open Source untuk Perusahaan: Sample Case E-Learning System - Win Ce; Gisella Febrina Alam (ComTech: Computer, Mathematics and Engineering Applications, 2011)
High increment of information system needs for company goes in line with the high demands of increasingly competitive and rivalry of industry. Corporate investment needs automatically increase to meet the demanding needs of this system. New developments in systems and technology can not be ignored by companies because it gives a very high economic boost in the competition. On the other hand, in line with the development of information systems is the development of Open Source applications as a cheaper alternative for enterprise use. With so many alternative of Open Sources requires companies to be more observant of selecting the best applications that meet the company needs and can be quickly implemented. This study presents the best approaches to select the best Open Source applications for companies, such as literature review, implementation and evaluation of e-learning Open Source application.